Оптимальное управление точностью обработки деталей в условиях АСУ - Кантор В. И.; Анисифоров О. Н.; Алексеева Г. Н.; Васильев А. М.; Дащенко А. И. (Москва, Машиностроение, 1981)
Авт. указаны на обороте тит. л.